Deletion of mitochondrial inorganic pyrophosphatase gene extends life span in haploid yeast (Saccharomyces cerevisiae) - Khandaker, AM; Koc, A (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Aging is a universal but poorly understood biological process and its underlying mechanisms are under intensive study. Mitochondria have a central role in the studies of aging hence they supply the majority of the organisms’ energy requirement from biological fuels. However, the role of mitochondria in the aging process is more complicated than the proposed theories of aging. We addressed a question by asking whether deletion to mitochondrial metabolism genes can extend life span in haploid cell of Saccharomyces cerevisiae (yeast). In this study, strains derived from the yeast open reading frame (ORF) deletions were screened through replicative aging assay in order to identify the mitochondrial metabolism genes that increase life span. This has resulted in the isolation of a long living (22% extended life span) mutant, ppa2Δ, which lack mitochondrial inorganic pyro phosphatase gene. The mitochondrial morphology of this long living mutant was analyzed by fluorescence microscopy. Compared to serpentine nature of wild type mitochondria, a different dynamics and distribution pattern was viewed, i.e. mitochondria were aggregated and formed colonies within the cytoplasm of this long lived cell. The aggregated mitochondrial mass was found to be intact from the young to old stage of life. Thus, this investigation reveals the longevity role of the mutant form of the gene PPA2 through an alteration of mitochondrial morphology. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(2): 69-76